Étude transversale sur le statut en vitamine D et ses déterminants chez les Cris du nord du Québec - Riverin Deschesnes, Bruno (Université Laval, 2014)
Aboriginal peoples affected by a nutrition transition and living at high latitudes are among the groups most at risk of vitamin D insufficiency. We conducted a cross-sectional study to examine the vitamin D status and associated factors among James Bay Cree. Data from 944 participants aged 15 years and above are from the Nituuchischaayihtitaau Aschii: A Multi-Community Environment and Health Longitudinal Study in Eeyou Istchee. According to the new reference level recently established, the vitamin D status in Cree was found to be suboptimal with nearly half (49%) of the sample population having inadequate concentrations for optimum bone health. We found that women and participants aged less than 40 years were more at risk of insufficiency. In a small sample of Cree children aged eight to 14 years, 43% of participants had concentrations inadequate for bone. Our findings support that it is essential that health professionals be informed in order to provide the necessary dietary counselling or other interventions at the population level to prevent the nutrition transition. Tableau d’honneur de la Faculté des études supérieures et postdoctorales, 2013-2014. Les nations autochtones du Canada vivant au nord et affectées par une transition nutritionnelle sont parmi les groupes ethniques les plus à risque de développer une carence en vitamine D. Nous avons mené une étude transversale afin de caractériser biologiquement le statut de la vitamine D et ses déterminants chez les Cris de la Baie James. Dans un échantillon aléatoire de 944 participants âgés de 15 ans et plus provenant de la Nituuchischaayhitaau Aschii: A Multi-Community Environment and Health Longitudinal Study in Iiyiyiun Aschii, une grande proportion (49%) des participants avaient des niveaux insuffisants en vitamine D selon le seuil récemment établi. La prévalence d’insuffisance en vitamine D était nettement plus marquée chez les femmes et chez les participants âgés de 15 à 39 ans. Dans un deuxième échantillon de 52 enfants âgés de huit à 14 ans, cette ...